SYNTHESIS AND BIOLOGICAL EVALUATION OF BENZIMIDAZOLE DERIVATIVES AS ANTIMICROBIAL AGENTS - SHINDE, VANDANA BABAN; RASKAR, MANISH ASHOK (International Journal of Current Pharmaceutical Research, 2019)
Objective: The present study aims to synthesize and biological evaluation of benzimidazole derivatives as antimicrobial agents. Methods: 2-Methylbenzimidazole react with ethyl-chloroacetate gives N1-Ethylacetate-2-methyl-benzimidazole (1), which on reaction with thiosemicarbazide gives N1-acetylthiosemicarbazide-2-methyl-benzimidazole (2). The compound (2) on dehydrative annulation by mineral acid gives N1-(2’-amino-5’-methylene)-1’,3’,4’-thiadiazole-2-methyl-benzimidazole(3), which on condensation with various aromatic and hetero aromatic aldehydes gives N1-(2-substituted-Benzylidene-imino-5’-methylene)-1’, 3’, 4’-Thiadiazole]-2-methyl-benzimidazole(4a-4l). Results: The reaction sequence involves microwave-induced preparation of N1-Ethylacetate-2-methyl-benzimidazole (1) from reaction of 2-methylbenzimidazole with ethyl-chloroacetate. Further reaction with thiosemicarbazide gives N1-acetylthiosemicarbazide-2-methyl-benzimidazole (2). The compound (2) on dehydrative annulation by sulfuric acid gives N1-(2’-amino-5’-methylene)-1’,3’,4’-thiadiazole-2-methyl-benzimidazole(3), which on condensation with various aromatic and hetero aromatic aldehydes gives N1-(2-substituted-Benzylidene-imino-5’-methylene)-1’, 3’, 4’-Thiadiazole]-2-methyl-benzimidazole(4a-4l). Which were characterized by IR and 1H NMR spectral data. Conclusion: All the synthesized compounds were screened for antimicrobial activity by cup plate method. Most of the derivatives showed good antimicrobial activity against Gram-Positive and Gram-negative bacteria.